2019
DOI: 10.1002/smll.201900950
|View full text |Cite
|
Sign up to set email alerts
|

Ultraminiature and Flexible Sensor Based on Interior Corner Flow for Direct Pressure Sensing in Biofluids

Abstract: Conventional pressure sensing devices are well developed for either indirect evaluation or internal measuring of fluid pressure over millimeter scale. Whereas, specialized pressure sensors that can directly work in various liquid environments at micrometer scale remain challenging and rarely explored, but are of great importance in many biomedical applications. Here, pressure sensor technology that utilizes capillary action to self‐assemble the pressure‐sensitive element is introduced. Sophisticated control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Continuous monitoring of variations in blood flow could be used to assess the status of vascular beds for various clinical scenarios, which is critical to patient recovery after reconstructive surgeries such as vessel anastomosis. [219] Therefore, there is an urgent need to fabricate flexible sensors that are capable of precisely and continuously monitoring blood flow in vivo. Boutry et al reported a pressure sensor that can wirelessly monitor arterial blood flow.…”
Section: Blood Flowmentioning
confidence: 99%
“…Continuous monitoring of variations in blood flow could be used to assess the status of vascular beds for various clinical scenarios, which is critical to patient recovery after reconstructive surgeries such as vessel anastomosis. [219] Therefore, there is an urgent need to fabricate flexible sensors that are capable of precisely and continuously monitoring blood flow in vivo. Boutry et al reported a pressure sensor that can wirelessly monitor arterial blood flow.…”
Section: Blood Flowmentioning
confidence: 99%
“…In order to simplify the structure, membraneless pressure methods have also been proposed [ 30 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. According to the measuring position, these methods can be generally classified into two categories.…”
Section: Introductionmentioning
confidence: 99%
“…The first category is direct measurement inside the microchannel, for example, the pressure-sensitive paint (PSP) method using luminescence emitted from air pressure-sensitive molecules [ 30 , 47 , 48 , 49 , 50 ] and the deformable elastic microballoon method [ 51 ], both of which are optical. The second category is based on a sealed side channel connected to the microchannel at the location where the pressure is to be measured, for example, the flexible liquid metal electrodes-based capacitive method [ 52 ] and trapped air compression methods [ 30 , 53 , 54 , 55 , 56 , 57 ]. Srivastava and Burns [ 54 ] developed an easy method for measuring the pressure of liquid and air by monitoring the movement of a liquid–air interface as it compresses air trapped inside a one-end-sealed side channel connected with a chamber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DOI: 10.1002/admt.202101126 materials, flexible electronics are generally classified into organic flexible electronics and inorganic flexible electronics, [20][21] that the former are enabled by employing intrinsically stretchable electronic materials, [22][23][24][25][26][27][28][29] while the latter depend on the use of hard inorganic electronic components and special structural designs (like inorganic serpentine interconnections and island-bridge structure) or liquid metal interconnections to obtain stretchability. [30][31][32][33][34][35][36] For inorganic flexible electronics, encapsulation serves as an essential fabrication step to keep the device's function stable and enhance biosafety. [37][38][39][40] Conventionally, direct casting encapsulation is generally used including pouring a liquid elastomeric encapsulation material onto the device and then directly curing it.…”
mentioning
confidence: 99%